2010
DOI: 10.1007/s00401-010-0785-8
|View full text |Cite
|
Sign up to set email alerts
|

Blood-derived iron mediates free radical production and neuronal death in the hippocampal CA1 area following transient forebrain ischemia in rat

Abstract: Abnormal brain iron homeostasis has been proposed as a pathological event leading to oxidative stress and neuronal injury under pathological conditions. We examined the possibility that neuronal iron overload would mediate free radical production and delayed neuronal death (DND) in hippocampal CA1 area after transient forebrain ischemia (TFI). Mitochondrial free radicals (MFR) were biphasically generated in CA1 neurons 0.5-8 and 48-60 h after TFI. Treatment with Neu2000, a potent spin trapping molecule, as wel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
59
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 74 publications
(62 citation statements)
references
References 60 publications
1
59
0
Order By: Relevance
“…Our results support the hypothesis that ironmediated BBB disruption in the CA1-2 areas contributes to delayed neuronal cell death in the CA1 following TFI, for the time course of BBB opening is similar to the kinetics of free radical generation in CA1 neurons; free radical levels are highest 8 and 48 h after TFI Park et al, 2010). Iron overload was observed in the endothelium within 30 min after TFI, which resulted in delayed iron overload and free radical production in the CA1 neurons (Park et al, 2010).…”
Section: Levels Of [supporting
confidence: 84%
See 2 more Smart Citations
“…Our results support the hypothesis that ironmediated BBB disruption in the CA1-2 areas contributes to delayed neuronal cell death in the CA1 following TFI, for the time course of BBB opening is similar to the kinetics of free radical generation in CA1 neurons; free radical levels are highest 8 and 48 h after TFI Park et al, 2010). Iron overload was observed in the endothelium within 30 min after TFI, which resulted in delayed iron overload and free radical production in the CA1 neurons (Park et al, 2010).…”
Section: Levels Of [supporting
confidence: 84%
“…We have previously shown that iron overload is evident early in CA1 pyramidal neurons after TFI, in turn mediating free radical production and delayed neuronal degeneration Park et al, 2010). In this context, iron overload likely contributes to degeneration of CECs, and opening of the BBB.…”
Section: Region-specific Iron Overload-mediated Free Radical Productimentioning
confidence: 92%
See 1 more Smart Citation
“…Iron has been found to be required for long-term potentiation in hippocampal CA1 neurons and it is known to participate in the stimulation of calcium release through ROS produced via the Fenton reaction and triggering the activation of cellular signaling pathways [9,10]. These results support a coordinated action between iron and calcium in synaptic plasticity and raise the possibility that elevated iron levels may contribute to neuronal degeneration through excessive intracellular calcium increase caused by iron-induced oxidative stress [11].…”
Section: Introductionmentioning
confidence: 80%
“…Recently, the activation of the GluK1 receptor was reported to play a protective role in cerebral ischemia-reperfusion injury by inhibiting a JNK3 pathway mediated by the GluK2 receptor (11). Since NEU proficiently rescues animals from ischemia-reperfusion injury (4,12), it is highly possible that NEU activity is specific to GluK1 receptors. This subtype specificity of NEU action may explain why NEU has greater efficacy and potency (4) than other chemicals with NMDA-receptor antagonism and anti-oxidation action such as dexanabinol (13) and 1-aminocyclopropanecarboxylic acid (14).…”
Section: Neu2000 Potentiates a Kainate Response In Mouse Cortical Neumentioning
confidence: 99%